Simulating the hydrology of small coastal ecosystems in conditions of limited data - Smakhtin, Vladimir U.; Piyankarage, Sujeewa C.; Stanzel, P.; Boelee, Eline (International Water Management Institute, 2004)
The impacts of water resources and irrigation development need to be quantified in order to understand the environmental costs of such development activities. Complex data-intensive simulation methods are normally used for this purpose in the developed world. However, lack of reliable data prohibits the use of such models in developing countries where it is more practical to apply models with less data requirements. The report illustrates three applications of simple and pragmatic simulation models to small coastal water bodies in Sri Lanka and South Africa.